Residual and recurrent shunts after implantation of Cook detachable duct occlusion coils. Issue 3 (1st March 1998) - Uzun, O; Dickinson, D; Parsons, J; Gibbs, J L
Abstract : Objective: To assess the presence and outcome of Doppler detectable shunts following implantation of the Cook detachable PDA coil. Design: Prospective study. Setting: Tertiary paediatric cardiac centre. Patients: 76 consecutive patients undergoing coil implantation (80 procedures). Main outcome measures: Detection and colour Doppler echocardiographic appearance of residual or recurrent shunts, the timing of the appearance of recurrent shunts, and the time taken for spontaneous resolution of these shunts. Results: Immediate occlusion was achieved in 52 patients. At one month 63 patients had complete occlusion and after three months the duct was completely occluded in 67 patients. In 27 cases small residual shunts were detected on echocardiography 10 minutes after the completion of the implantation procedure; 15 of these had resolved by 24 hours and 20 had resolved by three months. Recurrent shunts were detected after apparent initial complete occlusion in 11 cases 24 hours after coil implantation and in two cases one month after the procedure. Six recurrent shunts resolved on later follow up. Residual shunts appeared as single jets after implantation of a single coil, but up to three separate jets were detected after implantation of multiple coils. Conclusions: Spontaneous resolution of small residual shunts occurs in most patients. The recurrence of small shunts after apparent complete occlusion suggests that recanalisation of the duct may occur in a small percentage of patients up to one month after occlusion. Residual shunts may take the form of multiple residual jets that may require implantation of further coils to achieve complete duct occlusion.